Single BNT162b2 vaccine dose produces seroconversion in under 60 s cohort. Issue 47 (16th November 2021) - Shachor-Meyouhas, Yael; Hussein, Khetam; Szwarcwort-Cohen, Moran; Weissman, Avi; Mekel, Michal; Dabaja-Younis, Halima; Hyams, Gila; Horowitz, Netanel A.; Kaplan, Marielle; Halberthal, Michael
Highlights: Serological testing was performed 21 days after first BNT162b2 dose of 1898 Healthcare Workers. Younger age (<60) was associated with increased likelihood of seroconversion. Positive serology among females was greater than males. Delayed second BNT162b2 dose in under 60 s population may be justified if necessary. Abstract: Introduction: The coronavirus disease 2019 (COVID-19) pandemic has led to worldwide vaccination development efforts. In December 2020 the Pfizer BNT162b2 vaccine was approved in the United States. This study describes the first BNT162b2 vaccine dose effect on a large cohort. Methods: This retrospective study examined first vaccine dose effect on serology and investigated the associations between seroconversion and age or sex. Results: Serological blood tests were performed on 1898 participants following first vaccine dose; 81% were tested on day 21, before receiving the second dose (mean age 47.5 ± 12.45; median 47.7, range 18–90). Positive serology was found in 92.7% of day 21 tests. Overall positivity was 86.8%, with rates increasing from 2.5% within 1–14 days to 89.8% (14–20 days), 92.7% (21 days), and 95.9% (>21 days). Mean antibody levels 21 days after first dose were 64.3 ± 33.01 AU/ml, (range 15–373 AU/ml, median 61 AU/ml). Seropositivity was greater in females than males (88.3%. vs 83.3% respectively, p < 0.001; OR1.515; 95% CI 1.152–1.994). Older age > 60 years was associated with decreased likelihood of seropositivity (p < 0.001; OR 0.926; 95% CI 0.911–0.940). Longer time between first vaccination and serology tests was associated with increased likelihood for seropositivity (p < 0.001; OR 1.350; 95% CI 1.298–1.404). Conclusions: The high seroconversion rate following first BNT162b2 dose among individuals < 60 may justify delayed delivery of the second dose, potentially help relieve the worldwide vaccination supply shortage, enable vaccination of twice this population within a shorter period, and ultimately reduce COVID-19 contagion.